2022
DOI: 10.1186/s12891-022-05730-x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal TNS3 gene methylation in patients with congenital scoliosis

Abstract: Background Congenital scoliosis (CS) is a congenital deformity of the spine resulting from abnormal and asymmetrical development of vertebral bodies during pregnancy. However, the etiology and mechanism of CS remain unclear. Epigenetics is the study of heritable variations in gene expression outside of changes in nucleotide sequence. Among these, DNA methylation was described first and is the most characteristic and most stable epigenetic mechanism. Therefore, in this study, we aim to explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Recent studies showed that aberrant DNA methylation might be linked with the pathogenesis of CS. As compared with healthy individuals, CS patients showed hypermethylation in KAT6B , TNS3 , IGHG1 , IGHM , IGHG3 , RNF213 , and GSE1 , and hypomethylation in SORCS2 , COL5A1 , GRID1 , RGS3 , and ROBO2 [ 143 145 ]. Moreover, DNA methylation is a critical mechanism in the process of genomic imprinting, an epigenetic mode of inheritance in which genes are expressed exclusively from one parental chromosome, depending on their parental origin.…”
Section: The Role Of Environmental Factors and Epigenetics In Congeni...mentioning
confidence: 99%
“…Recent studies showed that aberrant DNA methylation might be linked with the pathogenesis of CS. As compared with healthy individuals, CS patients showed hypermethylation in KAT6B , TNS3 , IGHG1 , IGHM , IGHG3 , RNF213 , and GSE1 , and hypomethylation in SORCS2 , COL5A1 , GRID1 , RGS3 , and ROBO2 [ 143 145 ]. Moreover, DNA methylation is a critical mechanism in the process of genomic imprinting, an epigenetic mode of inheritance in which genes are expressed exclusively from one parental chromosome, depending on their parental origin.…”
Section: The Role Of Environmental Factors and Epigenetics In Congeni...mentioning
confidence: 99%